Structure and crystallization behavior of Al containing glasses in the CaO–B2O3–SiO2 system. Issue 24 (6th March 2017) - Han, Jiao; Lai, Yuanming; Xiang, Yao; Wu, Shuang; Zeng, Yiming; Yang, Hongwei; Mao, Yongyun; Yang, Yuwen
Abstract : The aim of the present work is to investigate the effects of Al2 O3 content on both the structure and crystallization behavior of CaO–B2 O3 –SiO2 (CBS) glass composition using NMR, FT-IR and DSC. Abstract : The aim of the present work is to investigate the effects of Al2 O3 content on both the structure and crystallization behavior of CaO–B2 O3 –SiO2 (CBS) glass composition using NMR, FT-IR and DSC. The density experimental results showed that the density ( ρ ) of glasses decreased linearly with increasing Al2 O3 content, while the molar volume ( V m ) of the glasses increased linearly. The NMR revealed that the Al occurred in the forms of Al IV, Al V and Al VI units. With the increasing Al2 O3 content, the amount of Al species show little change, the relative amount of B IIIa and B IIIs units increases while the B IV units decrease, and the Q 4 structural units increases clearly but the Q 3 decreases. Further, crystallization peaks of CBS glasses shift to higher temperatures, indicating that Al2 O3 addition can suppress crystallization of CBS glasses.